Konflik Kebijakan Tenaga Kesehatan Non PNS dengan Peraturan Perundang-Undangan - Sarif, Nadira Nestria; Budhiartie, Arrie; Syam, Fauzi (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
There is a conflict of norms in the Laws and Regulations on Non-Civil Servant Health Worker Policy, namely between the ASN Law and the Indonesian Minister of Home Affairs Number 79 of 2018 concerning Regional Public Service Agencies. The research method used is a normative juridical research method. The theories used are the theory of legislative hierarchy and the theory of legal certainty. Data collection techniques with literature studies. The data that has been obtained is then analyzed qualitatively to obtain descriptive research results. Based on the results of the study, it is known that the Conflict of the Policy of Non-Civil Servant Health Workers with the Laws and Regulations on Health is between the ASN Law which states that ASN personnel only consist of civil servants and Government Employees with Employment Agreements, but the Minister of Home Affairs of the Republic of Indonesia No. 79 of 2018 concerning Regional Public Service Agencies, With the existence of the Permendagri, public health centers with BLUD status can appoint employees with Non-Civil Servant status who can be employed on a permanent basis or contract, this certainly causes a conflict of norms that does not provide legal certainty about the existence of the non-civil servant health workers. To resolve the conflict of norms, the principle of Lex Superiori derogate Legi inferiori is used, which means that higher laws negate the enactment of lower laws, so the provisions that must be implemented are Law Number 20 of 2023 concerning the State Civil Apparatus. Here, the role of the local government is very necessary in collecting data on Non-Civil Servants in the health center for proposals to become PPPK or civil servants according to applicable regulations.